1991
DOI: 10.1055/s-2007-1025460
|View full text |Cite
|
Sign up to set email alerts
|

Die Creatin-Kinase MM in der Perinatalperiode

Abstract: One hundred eight newborns (gestational age 36 + 1.8 weeks and birth weight 2860 +/- 240 g) had muscle type Creatine-Kinase activity (CK-MM) assayed immediately after birth (CK-I) and serially at 6-10 h (CK-II), 20-30 h (CK-III) and 40-60 h (CK-IV) of age. Using statistical Regression analysis, CK-MM levels were correlated to four perinatal parameters: gestational age, birth weight, neonatal acidosis (pH less than 7.15), mode of delivery (vaginal/cesarean section). It was observed that CK-MM activity was depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…38 Amato et al reported markedly elevated levels of CK-MM following vaginal delivery especially if complicated by forceps, vacuum, and breech presentation. 39 In the NYS study, several referred newborns had shoulder dystocia, shoulder dislocation, or were born by breech delivery. Shoulder dystocia was reported in 24% of referred newborns as compared to approximately 1-10% in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…38 Amato et al reported markedly elevated levels of CK-MM following vaginal delivery especially if complicated by forceps, vacuum, and breech presentation. 39 In the NYS study, several referred newborns had shoulder dystocia, shoulder dislocation, or were born by breech delivery. Shoulder dystocia was reported in 24% of referred newborns as compared to approximately 1-10% in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent studies have shown that transiently elevated CK-MM in the early newborn period could be a significant cause of false-positive NBS referrals. This is because, for most newborns, NBS DBSs are collected in the first 24 to 48 h of life when elevated CK-MM resulting from traumatic birth events (e.g., the use of forceps, vacuum extraction, fractures, or a nuchal cord) may still be returning to normal [ 23 ]. The level of CK-MM in blood at the time of typical NBS may therefore be indistinguishable among newborns with DMD and those recovering from birth trauma [ 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%